Polityczność kontroli konstytucyjności aktów normatywnych w systemie prawa polskiego — wybrane problemy - Naleziński, Bogumił; Holecher, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The first part of the paper is devoted to the analysis of the concept of politicalness. Its purpose is to distinguish different meanings of politicalness, along with their reference to the activities of the Polish Constitutional Tribunal in the sphere of constitutional review. The second part of the study concerns the factors determining the Constitutional Tribunal’s entering into the prohibited sphere of politicalness, and consequently the politicization of its functioning. These factors are related toboth constitutional control standards of the law and its subject matter. The authors also attempted to indicate the material and procedural elements of the activities of the constitutional court that may serve to protect the unpolitical nature of this judicial authority.
Keywords: the political; limited politics; particular politics; constitutional review; program norms; Constitutional Tribunal